Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Step-by-step explanation:
Simply Equation 1
R. H. S
6x^2 -x +3-2x^2-8
==> 6x^2-2x^2 -x +3-8
==> 4x^2-x-5 .....(1)
Simply equation 2
L. H. S
4x^2+2x-5-3x
==> 4x^2 +2x-3x-5
==> 4x^2-x-5 ....(2)
Since here, RHS = LHS
both eqn (1) = eqn(2)
hence they are equal.
Answer:
yes they are equal
Step-by-step explanation:
for the equation [tex]4x^{2} +2x-5-3x[/tex] you're going to collect like terms
2x-3x=5x
so your final equation is [tex]4x^{2} -x-5[/tex]
for the equation [tex]6x^{2} -x+3-2x^{2} -8[/tex] you're going to collect like terms
[tex]6x^{2} -2x^{2} =4x^{2}[/tex]
then you're going to calculate the difference
3x-8=-5
so your final equation is [tex]4x^{2} -x-5[/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.